Characterization of a phytoplasma associated with frogskin disease in cassava - Álvarez, E.; Mejía de los Ríos, J.F.; Llano Rodríguez, Germán Alberto; Loke, John Bernard; Calari, A; Duduk, B; Bertaccini, A (Scientific Societies, 2009)
Cassava frogskin disease (CFSD) is an economically important root disease of cassava (Manihot esculenta) in Colombia and other South American countries, including Brazil, Venezuela, Peru, Costa Rica, and Panama. The roots of severely affected plants are thin, making them unsuitable for consumption. In Colombia, phytoplasma infections were confirmed in 35 of 39 genotypes exhibiting mild or severe CFSD symptoms either by direct or nested polymerase chain reaction (PCR) assays employing ribosomal (r)RNA operon primer pairs. The CFSD-associated phytoplasmas were identified as group 16SrIII strains by restriction fragment length polymorphism (RFLP) and sequence analyses of amplified rDNA products, and results were corroborated by PCRs employing group 16SrIII-specific rRNA gene or ribosomal protein (rp) gene primers. Collectively, RFLP analyses indicated that CFSD strains differed from all phytoplasmas described previously in group 16SrIII and, on this basis, the strains were tentatively assigned to new ribosomal and ribosomal protein subgroups 16SrIII-L and rpIII-H, respectively. This is the first molecular identification of a phytoplasma associated with CFSD in cassava in Colombia.